Night and shift work patterns and incidence of type 2 diabetes and hypertension in a prospective cohort study of healthcare employees - Viklund, Andreas; Andersson, Tomas; Selander, Jenny; Kader, Manzur; Albin, Maria; Bodin, Theo; Härmä, Mikko; Ljungman, Petter; Bigert, Carolina (Scandinavian Journal of Work, Environment & Health, 2023)
' ' OBJECTIVES ': 'This study aimed to evaluate effects of night and shift work patterns on type 2 diabetes (T2D) and hypertension in a longitudinal study, with detailed information on working hours. ' ' METHODS ': 'The cohort comprised about 28 000 nurses and nursing assistants employed for more than one year 2008–2016 in Stockholm, Sweden. The employee register held detailed individual information on daily working hours. Information on diagnoses came from national and regional registers. Hazard ratios (HR) and confidence intervals (CI) were estimated by discrete-time proportional hazard models, adjusting for sex, age, country of birth, and profession. ' ' RESULTS ': 'During follow-up in 2013–2017, we identified 232 cases of T2D and 875 of hypertension. We observed an increased risk of T2D, but not hypertension, among employees who worked only night shifts the previous year (HR 1.59, 95% CI 1.02–2.43) and those with intensive shift work (>120 afternoon and/or night shifts the previous year: HR 1.67, 95% CI 1.11–2.48) compared to only day work. There was a non-significantly increased risk of T2D related to mixed day and afternoon shifts (HR 1.34, 95% CI 0.97–1.88). We observed tendencies in increased risk of T2D related to frequent spells of ≥3 consecutive night shifts and with number of years with exclusive (but not mixed) night work. ' ' CONCLUSIONS ': 'Permanent night work and frequent afternoon and/or night shifts were associated with an increased risk of T2D the following year, but not hypertension. The T2D risk was, to some extent, affected by frequent spells of several night shifts in a row and by cumulative years with permanent night work.
Keywords: diabetes; healthcare; healthcare worker; hypertension; night shift; night work; prospective cohort study; shift work; shift work pattern; type 2 diabetes